1984
DOI: 10.1152/ajpheart.1984.246.6.h776
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial alterations due to free-radical generation

Abstract: Oxygen-derived free radicals have been proposed as general mediators of tissue injury in a variety of disease states. Recent interest has focused on the possibility that free radicals may be involved in ischemic myocardial damage. However, the exact types of damage that result from myocardial exposure to free radicals remains to be established. The purpose of this study was to evaluate the effects of superoxide and hydroxyl radicals on myocardial structure and function in an isolated perfused rabbit interventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
2

Year Published

1985
1985
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(104 citation statements)
references
References 0 publications
3
99
0
2
Order By: Relevance
“…Secondly, during myocardial ischemia, there is loss ofthe enzymes, superoxide dismutase, catalase, and glutathione peroxidase (47, 5 1), which could protect the heart from oxygen-derived free radicals. The autoxidation of catecholamines could provide another source of free radicals (52,53).…”
Section: Oxygen-derivedfree Radicalsmentioning
confidence: 99%
“…Secondly, during myocardial ischemia, there is loss ofthe enzymes, superoxide dismutase, catalase, and glutathione peroxidase (47, 5 1), which could protect the heart from oxygen-derived free radicals. The autoxidation of catecholamines could provide another source of free radicals (52,53).…”
Section: Oxygen-derivedfree Radicalsmentioning
confidence: 99%
“…It has been proposed that a major portion of this reflow injury occurs secondary to the generation of oxygen free radicals (5). During the past decade indirect evidence from studies demonstrating the protective effects of free radical scavengers has suggested that reactive free radicals are formed both during ischemia and, more importantly, during postischemic reperfusion (5)(6)(7)(8)(9)(10). Also, reactive oxygen radicals have been shown to produce myocardial damage (6).…”
mentioning
confidence: 99%
“…All the ascorbic acid derivatives were characterized by 1 C NMR spectra were recorded on a Varian Gemini 300 spectrometer, operating at 75.46 MHz for the 13 C resonance. The samples were dissolved in DMSO-d 6 or CDCl 3 chemical shift values are in ppm, referred to TMS.…”
Section: B Methodsmentioning
confidence: 99%